Fence: striking distance : an original novel - Brennan, Sarah Rees (Little, Brown and Company, 2020)
"The boys of Kings Row are assigned a course of team building exercises to deepen their bonds. It takes a shoplifting scandal, a couple of moonlit forest strolls, and a whole lot of introspection for the team to realize they are stronger together than they could ever be apart"--